Los viajes a las Indias: el descubrimiento de las palabras - Gil García, Teresa (Revista de Filología Románica, 2006)
This work explains the acquisition process of neologism referred to the New World realities, incorporated to the Italian and Spanish languages during the XVIth century. As a significant example, it shows the route of the words caimán and tiburón.